Modelling and decentralized adaptive tracking control of a quadrotor UAV - Mohammadi, M.; Mohammad Shahri, Alireza (2013 First RSI/ISM International Conference on Robotics and Mechatronics (ICRoM), 2013)
The dynamics of Unmanned Aerial Vehicles (UAV) have special features that can complicate the process of designing a trajectory tracking controller. Unknown nonlinearities, strong coupling between subsystems, parametric uncertainties in model, unknown physical parameters, nonparametric uncertainties in inputs, outputs disturbances like wind gust and sometimes underactuated mechanical system are some of these basic problems. In this paper, after modelling the quadrotor as a Vertical Take Off and Landing UAV (VTOL UAV) a nonlinear adaptive controller is designed, to solve trajectory tracking problem in the presence of all problems mentioned above. In this approach, the control of quadrotor is performed by using decentralized adaptive controllers in the inner (attitude control) and outer (translational movement control) loops. The outer loop generates the instantaneous desired angles for inner loop. The inner loop stabilizes the orientation of the vehicle. Inverse kinematic of robot is used to convert outputs of the outer loop to inputs of the inner loop. A robust parameter identifier estimates the required parameters for outer control loops. Simulations are carried out to illustrate the robustness and tracking performance of the controllers.